Der-p2 (Dermatophagoides pteronyssinus) allergen-like protein from the hard tick Ixodes ricinus - a novel member of ML (MD-2-related lipid-recognition) domain protein family. - Plchová, Jana (Jihočeská univerzita, 2012)
A family of ML (MD-2-related lipid-recognition) domain containing proteins contains immune-related molecules. It does not belong among well-studied protein family in ticks although its occurence is quite often. Generally, ML proteins are involved in innate immunity processes, lipid binding and transport. A novel member of the ML protein family, Der-p2 allergen-like protein was isolated from Ixodes ricinus and characterized for the first time.
Der-p2 (Dermatophagoides pteronyssinus) allergen-like protein from the hard tick Ixodes ricinus - a novel member of ML (MD-2-related lipid-recognition) domain protein family.
Keywords: tick; Ixodes ricinus; ML protein family; allergen-like protein; tick; Ixodes ricinus; ML protein family; allergen-like protein